Hybrid Justice : The Extraordinary Chambers in the Courts of Cambodia - Ciorciari, John D. (John David); Heindel, Anne (Book collections on Project MUSE., 2014)
A definitive scholarly treatment of the ECCC from legal and political perspectives.